Oscar Wilde and Authorialism - Selleri, Andrea (Authorship, 2014)
This essay introduces the concept of “authorialism” to characterise the critical orientation that sees literary works primarily as actions on the part of their authors rather than as linguistic objects, using the early reception of Oscar Wilde’s works as a case study. It is argued that authorialism was the dominant tendency in 1875-1900 Anglophone criticism, and that it has characterised assessments of Wilde’s works to this day. The method has the advantage of finding coherence in literary works, which is useful in assessing matters of value; the textual features of Wilde’s writings, however, resist authorialist readings by not featuring the expected coherence.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE4MjUvYWoudjNpMi4xMDg2